PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA KDRT PUTUSAN NOMOR 203/Pid.Sus/2022/PN NGW - Ragillia, Cynthia Selvidie; Santoso, Bambang (Verstek, 2025)
This study aims to determine the balance of the judge's considerations in Decision Number 203/Pid.Sus/2022/PN Ngw is in accordance with the provisions of the Criminal Procedure Code. This research is a normative legal research that has a prescriptive nature. The approach used in this study is a case approach. The legal materials used to write this law were obtained from secondary legal materials andprimary legal materials. The legal material collection technique used by the author is a literature study. The legal material analysis technique by processing legal materials using the syllogistic deduction method. The results of the research and discussion show that the judge's considerations in sentencing the defendant in Decision Number 203/Pid.Sus/2022/PN Ngw are in accordance with the provisions as stated in Article 183 of the Criminal Procedure Code.